AKTUALISASI SISTEM NILAI DALAM MEMBANGUN BUDAYA ORGANISASI LEMBAGA PENDIDIKAN Studi Multikasus di MAN 2 Tulungagung dan SMAN 1 Boyolangu Tulungagung - Khomsiyah, Indah; Chotimah, Chusnul (Jurnal Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2015)
Characteristics of organizational culture between one institution to another is not the same, and each uses a basic value as a reference act; value is an intangible aspect that can move the organizational elements forming organizational culture in a long time. In terms of organizational socialization values, there had to be obstacles, but can be solved by using effective communication.Kata kunci: Nilai, budaya organisasi, pendidikan